'Delivery' of an anal angiofibroma. Issue 754 (August 1988) - Kurzel, R. B.; Enriquez, S.
Abstract : A case is presented of an anal angiofibroma. This is the first report of this tumour in a pregnant patient. The tumour appeared to grow in size during the pregnancy.